SISTEM INFORMASI PEMBAYARAN PASIEN NON BPJS PADA UPTD PUSKESMAS - Munifah (Jurnal Ilmiah Sistem Informasi, 2023)
The implementation of cashier payments and cashier data processing at UPTD Puskesmas In order to support implementation activities at UPTD Puskesmas XYZ, a system is needed which is expected to make things easier for cashiers. This research is qualitative in nature with observational data collection techniques. This information system design method uses Prototype. The consequence of this exploration is that there is an online application that can assist with the installment interaction for non-BPJS patients. This application was made with the PHP programming language and the data set utilized is MySQL.